Filsafat Stoisisme dalam Perspektif Iman Orang Kristen - Remegises Danial Yohanis Pandie (Sekolah Tinggi Teologi Baptis Indonesia, 2023)
This paper refers to the philosophical, theoretical framework of Stoicism and its urgency for developing the Christian faith. Today many Christians experience degradation of control and self-mastery, resulting in internal conflicts within oneself and horizontal conflicts with others. The research method used is a literature study. In this study, researchers found that the philosophical theory of Stoicism, within certain limits, can be implemented in the lives of Christians through happiness, self-mastery, benevolence, teaching, self-improvement, and being grateful for the existing life. Regardless of the selfish attitude that appears, the best hope of every Christian is to be happy with what God is doing in their lives so that suffering, distress, or sadness is not a reason for Christians not to love or worship Jesus.